Compliance Disengagement in Research: Development and Validation of a New Measure - DuBois, James M. (Sci Eng Ethics, 2015)
In the world of research, compliance with research regulations is not the same as ethics, but it is closely related. One could say that compliance is how most societies with advanced research programs operationalize many ethical obligations. This paper reports on the development of the How I Think about Research (HIT-Res) questionnaire, which is an adaptation of the How I Think (HIT) questionnaire that examines the use of cognitive distortions to justify antisocial behaviors. Such an adaptation was justified based on a review of the literature on mechanisms of moral disengagement and self-serving biases, which are used by individuals with normal personalities in a variety of contexts, including research. The HIT-Res adapts all items to refer to matters of research compliance and integrity rather than antisocial behaviors. The HIT-Res was administered as part of a battery of tests to 300 researchers and trainees funded by the US National Institutes of Health. The HIT-Res demonstrated excellent reliability (Cronbach’s alpha = .92). Construct validity was established by the correlation of the HIT-Res with measures of moral disengagement (r = .75), cynicism (r = .51), and professional decision-making in research (r = −.36). The HIT-Res will enrich the set of assessment tools available to instructors in the responsible conduct of research and to researchers who seek to understand the factors that influence research integrity.